2018
DOI: 10.1177/0706743718762097
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and Preclinical Glycemic Control in Newly Diagnosed First-Episode Psychosis Patients

Abstract: FEP patients from a visible minority or who were victims of childhood physical abuse have higher levels of HbA1c at admission compared with other patients. This might suggest an increase in risk for the development of future DGM. If confirmed, preventive strategies could be tailored for these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…One study found that social determinants of health were inversely associated with glycated hemoglobin in first-episode psychosis [9]. However, patients had very short prior psychotropic treatment exposure and the cross-sectional design precluded the investigation of the impact of SES factors on treatment-related metabolic health evolution.…”
Section: Translational Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that social determinants of health were inversely associated with glycated hemoglobin in first-episode psychosis [9]. However, patients had very short prior psychotropic treatment exposure and the cross-sectional design precluded the investigation of the impact of SES factors on treatment-related metabolic health evolution.…”
Section: Translational Psychiatrymentioning
confidence: 99%
“…8 Service of General Psychiatry, Department of Psychiatry, Lausanne University Hospital, University of Lausanne, Prilly, Switzerland. 9 Service of Child and Adolescent Psychiatry, Department of Psychiatry, Lausanne University Hospital, University of Lausanne, Lausanne, Switzerland. 10 Service of Old Age Psychiatry, Department of Psychiatry, Lausanne University Hospital, University of Lausanne, Prilly, Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…12 Nineteen studies described the sample and together they included 13,976 participants (including 5656 healthy controls). The studies were done in USA, 15,20,24 Canada, 22,28,29 UK, 16 Italy, 12,13,27 Switzerland, 12 Poland, 1,17,23 Norway, 11,21 Spain, Netherlands, Germany, 24 Belgium, and France, 14 Brazil, 19 Turkey, 18 Australia, 26 and India. 25
Figure 1.PRISMA flow diagram.
…”
Section: Resultsmentioning
confidence: 99%
“…846 were excluded at the title and abstract level and 62 studies that met the inclusion criteria were retrieved and assessed at full text level. Twenty articles 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Figure 1) published between 2011 and 2021 met the criteria for our final review. The majority of these studies (n = 12) were cross-sectional, 14,[17][18][21][22][23][24][25][26][27][28][29] while seven were case-control studies, 1,11,13,15,16,19,20 and one study was prospective, monitoring the weight gain in the participants for a year.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have described factors affecting antipsychotic-induced weight gain in FEP patients, which can be theoretically translated as factors of glucose abnormalities ( 4 , 36 ). However, only a few studies have focused on the effect of early life events, either perinatal ( 20 , 22 25 ) or postnatal ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%